Agricultural Intensification, Environmental Conservation, Conflict and Co-Existence at Lake Naivasha, Kenya - Bollig, Michael; Kioko, Eric; Kuiper, Gerda (Africa-Europe Group for Interdisciplinary Studies, 2024)
This interdisciplinary volume provides a comprehensive and rich analysis of the century-long socio-ecological transformation of Lake Naivasha, Kenya. Major globalised processes of agricultural intensification, biodiversity conservation efforts, and natural-resource extraction have simultaneously manifested themselves in this one location. These processes have roots in the colonial period and have intensified in the past decades, after the establishment of the cut-flower industry and the geothermal-energy industry. The chapters in this volume exemplify the multiple, intertwined socio-environmental crises that consequently have played out in Naivasha in the past and the present, and that continue to shape its future.